2022
DOI: 10.3389/fgene.2022.894325
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of expression and prognostic value of key regulators for m7G RNA methylation in hepatocellular carcinoma

Abstract: N7-methylguanosine (m7G) modification on internal RNA positions plays a vital role in several biological processes. Recent research shows m7G modification is associated with multiple cancers. However, in hepatocellular carcinoma (HCC), its implications remain to be determined. In this place, we need to interrogate the mRNA patterns for 29 key regulators of m7G RNA modification and assess their prognostic value in HCC. Initial, the details from The Cancer Genome Atlas (TCGA) database concerning transcribed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…m7G regulates cellular proliferation and maturation, both of which have been associated to cancer development. A recent study discovered that changes in the process of programmed tumor cell death may enhance the focused therapeutic effect of LIHC ( 31 ). As a result, early detection and diagnosis of the condition are critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…m7G regulates cellular proliferation and maturation, both of which have been associated to cancer development. A recent study discovered that changes in the process of programmed tumor cell death may enhance the focused therapeutic effect of LIHC ( 31 ). As a result, early detection and diagnosis of the condition are critical.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study discovered that changes in the process of programmed tumor cell death may enhance the focused therapeutic effect of LIHC (31). As a result, early detection and diagnosis of the condition are critical.…”
Section: Lihc Clinical Treatment Is a Critical Clinical Problem Duementioning
confidence: 99%
“…In glioblastoma, a study constructed a signature by four m7G-related genes (TMOD2, CACNG2, PLOD3, and TMSB10) and could predict the prognosis of glioblastoma patients [ 14 ]. Li et al [ 15 ] identified m7G-related clusters that could predict the prognosis of hepatocellular carcinoma patients. Furthermore, in the field of urological tumors, three studies demonstrated the prognostic value of m7G-related mRNAs, lncRNAs and miRNAs in clear cell renal cell carcinoma [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The m 7 G modi cation is catalyzed by a highly conserved methyltransferase complex -methyltransferase like 1 (METTL1) and WD repeat domain 4 (WDR4) in mammalian [26,27]. Recent studies have found that METTL1/WDR4 mediated RNA m 7 G modi cation plays important biological roles in human malignancies, such as cancers in the liver, colorectal, esophageal, bladder and lung [22,28,29]. Despite its functional importance in the aforementioned multiple solid tumors, the precise role and regulatory mechanism of METTL1/WDR4 in AML leukeamogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%